Fasciola gigantica: Production and characterization of a monoclonal antibody against recombinant cathepsin B3 - Anuracpreeda P. (2014)
A number of monoclonal antibodies (MoAbs) against a recombinant cathepsin B3 (rCatB3) of Fasciola gigantica were produced in BALB/c mice. Reactivity and specificity of these MoAbs were assessed by indirect ELISA and immunoblotting techniques. Six stable clones, namely 1C4, 1E9, 2E5, 2F9, 5B4, 5D7 were obtained. All MoAbs reacted with rCatB3 at molecular weight (MW) 37kDa as well as the glycosylated peptide at 55-75kDa and with the native CatB3 at MW 37kDa in WB extracts of metacercariae (Met) and newly excysted juveniles (NEJ). It was found to be IgG1 and λ light chain isotypes. Immunolocalization of CatB3 in metacercariae, NEJ, 4-week-old juvenile and adult F. gigantica performed by immunoperoxidase technique by using these MoAbs as probes indicated that CatB3 was present in high concentration in the caecal epithelium and caecal lumen of the Met and NEJ, but not in the 4-week-old juvenile and adult fluke. The MoAbs show no cross-reactions with antigens of other parasites including Gigantocotyl explanatum, Eurytrema pancreaticum, Paramphistomum cervi, Schistosoma spindale, S. mansoni, Haemonchus placei and Setaria labiato-papillosa. Thus, it is possible that these MoAbs could be a good candidate for immunodiagnosis of fasciolosis. © 2010 Elsevier Inc.